Indiana Cancer Pain and Depression (INCPAD) Trial Design of a Telecare Management Intervention for Cancer-Related Symptoms and Baseline Characteristics of Study Participants - Kroenke, Kurt (2009)
OBJECTIVE: Pain and depression are two of the most prevalent and treatable cancer-related symptoms, each present in at least 20-30% of oncology patients. Both symptoms, however, are frequently either unrecognized and/or undertreated. The objective is to describe a telecare management intervention delivered by a nurse-psychiatrist team that is designed to improve recognition and treatment of pain and depression. The enrolled sample is also described. METHOD: The Indiana Cancer Pain and Depression (INCPAD) study is an NCI-sponsored randomized clinical trial. A total of 405 patients with cancer-related pain and/or clinically significant depression from 16 urban or rural oncology practices throughout Indiana have been enrolled and randomized to either the intervention or a usual care control group. Intervention patients receive centralized telecare management coupled with automated home-based symptom monitoring. Outcomes will be assessed at 1, 3, 6 and 12 months by research assistants blinded to treatment arm. RESULTS: Of 4465 patients screened, 2185 (49%) endorsed symptoms of pain or depression. Of screen-positive patients, about one-third were ineligible (most commonly due to pain or depression not meeting severity thresholds, or pain that is not cancer-related). Of the 405 patients enrolled, 32% have depression only, 24% pain only, and 44% both depression and pain. At baseline, participants report an average of 16.8 days out of the past 4 weeks in which they were confined to bed or had to reduce their usual activities by ≥ 50% due to pain or depression. Also, 176 (44%) report being unable to work due to health reasons. CONCLUSIONS: When completed, the INCPAD trial will test whether centralized telecare management coupled with automated home-based symptom monitoring improves outcomes in cancer patients with depression and/or pain. Findings will be important for both oncologists and mental health clinicians confronted with oncology patients' depression or pain.